Assessment of the effectiveness of exercise interventions in the treatment of PTSD: based on a systematic evaluation and meta-analysis - Fang, Yifan; Zhang, Qilin; Lin, Zhiyi (Frontiers in Psychology, 2026)
BackgroundPhysical exercise is increasingly recognized for its potential to alleviate symptoms of post-traumatic stress disorder (PTSD). However, uncertainty remains regarding which exercise modalities are most effective, optimal prescription parameters, and which patient populations benefit most. This study systematically evaluated the effects of various exercise interventions on PTSD symptoms, aiming to provide an evidence base for personalized treatment strategies.MethodsWe conducted a systematic search of PubMed, APA PsycINFO, Embase, Cochrane Library, and Web of Science for randomized controlled trials (RCTs) examining exercise interventions in patients with PTSD. The search was completed in November 2024, and 14 RCTs meeting eligibility criteria were included. The study followed PRISMA guidelines and was registered in PROSPERO (CRD420250652205). A random-effects model was used for meta-analysis, with subgroup analyses performed to explore heterogeneity.ResultsThe meta-analysis showed that exercise interventions significantly reduced PTSD symptoms compared to control conditions (SMD = −0.35, 95% CI: −0.56 to −0.15, p < 0.05). Subgroup analyses indicated that yoga (SMD = −0.56, 95% CI: −0.85 to −0.27, p < 0.001) and resistance training (SMD = −0.38, 95% CI: −0.72 to −0.03, p = 0.031) were particularly effective. The most beneficial intervention protocol consisted of sessions delivered three times per week for 30–60 min, over a 12-week period. Additionally, female patients appeared to derive greater benefit from exercise interventions (SMD = −0.41, 95% CI: −0.76 to −0.06, p = 0.020).ConclusionThis review supports the use of structured exercise, especially yoga and resistance training, as an effective adjunctive intervention for PTSD. The findings inform evidence-based recommendations for clinical practice, including optimal dosing and population-specific considerations. Future research should integrate body-oriented frameworks such as psychomotor therapy to further elucidate mechanisms and personalize exercise-based approaches in trauma recovery.